The Big Change : America Transforms Itself, 1900-1950 - Allen, Frederick Lewis 1890-1954 (New York Harper & Brother Publishers, 1952)
A survey of major changes in American life and ideas during the first half of the twentieth century, focusing on economic expansion and its influence on the American standard of living, thinking, and citizenship.
Include Appendix and Index
Keywords: United States -- Social conditions -- Civilization